(untitled) (Damascus University Journal for legal sciences, 2025)
The beginning of human life “legally” is defined in civil law as “the birth of man”, as for penal, human birth did not go beyond conflicting legal opinions that neglected the fact that the fetus has a soul. and that this fetus may be subject to acts of abuse that are not criminalized by law. Death was also known for a long time as the cessation of the heart and breathing, but, with the development of medicine, the so-called brain death has been known, so there are many opinions between supporters and opponents of it. However, his recognition entailed legal problems in adapting this important incident between killing and harm if brain death was the result of a sinful assault.